Contrasting trends in regional arctic destinational and transit shipping - Lasserre, Frédéric (East-West Center, 2021)
Ever since the impact of climate change on Arctic sea ice began to be discussed in international forums at the turn of the century, several comments were published to the effect that diminishing sea ice would quickly translate into the development of massive transit routes across the Northwest Passage (NWP), the Northern Sea Route (NSR) and the Arctic Bridge linking Churchill on the shores of Hudson Bay and Murmansk. Twenty years later, Arctic shipping did indeed expand significantly, but the actual picture is significantly different from what analysts projected. Destinational traffic appears to be the driver of Arctic shipping expansion, while transit traffic remains marginal. What are the main features of Arctic shipping presently, and how did the industry adapt, depending on the area? Results show contrasting evolutions along the NSR, in the Canadian Arctic, and in Greenlandic waters. This chapter is based on the analysis of figures from three different sources, which implies methodological issues since the data does not display the same elements (Lasserre and Alexeeva, 2015; Lasserre 2019). In the Russian Arctic, data about vessel movements and characteristics were gathered from the Northern Sea Route Administration1 and from the Center for High North Logistics. For the Canadian Arctic, the Ministry of Transportation agency for the Northern Canada Vessel Traffic Services Zone Regulations provided the author with annual detailed ship movements. For Greenlandic waters, data was provided by the Danish Joint Arctic Command based in Nuuk. 0